Health Education Through Illustrated Storybooks Affected the Bullying Knowledge of Primary School Students - Feoh, Fepyani Thresna; Muskananfola, Istha Leanni (STIKes Patria Husada Blitar, 2025)
Bullying has become more prevalent not only among secondary school (SMP and SMA) students but also in primary school (SD) students. Children's physical and psychological development in primary school are the most crucial aspects. However, many primary school students face physical and psychological pressure in social interactions due to bullying. However, they are rarely reported even though they have a detrimental effect on both victims and perpetrators. Bullying is still considered normal in social interactions and is used as a joke and a way to demonstrate strength. One of the causes is primary school students’ lack of comprehension of bullying.This research aimed to determine primary school students' knowledge about bullying before and after receiving health education and analyze the impact of bullying themed illustrated storybooks on primary school students’ knowledge in Kupang to prevent bullying behaviors. The quasiexperimental approach pre-test and post-test with one group design. There were 200 primary school students involved in intervention. The Wilcoxon test results show that the average respondents’ knowledge improvement after being provided with health education about bullying using illustrated storybooks was 78.5%, with a p-value of 0.000. Therefore, it can be concluded that health education using illustrated storybook positively impacts primary school (SD) students’ bullying knowledge in Kupang. Collaboration between various parties, including parents, teachers, schools, and nurses, will continue to provide education about bullying for elementary school children as an effort to prevent bullying behavior in elementary school children.